Chemical and cultural control of Ipomoea hederacea var. integriuscula in narrow‐row soybean in southwestern Japan. Issue 3 (13th June 2021) - Asami, Hidenori; Tachibana, Masaaki; Homma, Koki
Abstract: In Japan, the spread of morning glory ( Ipomoea spp.) in soybean fields has become a serious issue. To establish a control approach for Ipomoea species, this study considered the optimal system combining cultural and chemical control methods. Field experiments were conducted for 3 years to investigate the effects of no‐tillage compared with tillage seeding in narrow‐row soybean and of application timing of selective post‐emergence herbicides bentazone and fluthiacet‐methyl. The cumulative emergence of entireleaf morning glory ( Ipomoea hederacea [L.] Jacq. var. integriuscula A. Gray) in no‐tillage was 25–79% of that in tillage, and the initial growth was suppressed. In no‐tillage, the dry matter weight of I. hederacea var. integriuscula was suppressed compared to tillage methods. However, in no‐tillage, initial soybean growth was inferior, and reduction of the relative photosynthetic photon flux density (RPPFD) in the soybean canopy was delayed. A combination of selective post‐emergence herbicide applications at the second and fourth trifoliate leaf stages (TLS) of soybean was most effective in I. hederacea var. integriuscula suppression. The initial growth of soybean greatly fluctuated yearly, and the period when the RPPFD became less than 50% varied at the fourth through seventh TLS. Therefore, if the initial soybean growth is good, the end of the required period for weed control can be defined as the fourth TLS. No‐tillage cultivation combined with management to promote soybean growth, such as adequate soil moisture control by subirrigation systems, may be effective in controlling I. hederacea var. Integriuscula .